DEVELOPING ABILITY OF THE STUDENTS AT SMAN 1 SOE KABUPATEN TIMUR TENGAH SELATAN (TTS) NUSA TENGGARA TIMUR IN USING SIMPLE PRESENT TENSE THROUGH INTERVIEW - Liunokas Yanpitherszon (Institut Agama Islam Negeri Palopo, 2018)
The objective of this research was to find out the effectiveness of using interview in using the simple present tense. This research used pre experimental research method. The population of this research is first class of SMAN 1 Soe Kabupaten Timur Tengah Selatan (TTS) NTT. The total number of population is 142 students in four classes. The researcher used random sampling technique. There were 20 students as sample of the research. The writer took 5 students from each class. The instrument of the research was written test. The findings which gained through pre test and post test showed the significant development of students’ ability in using simple present tense. The total mean score of the students’ scores in pre test was 3.85 and post test was 6.8. The result t test shows that the “to” is bigger that “tt” (17.5 > 2.093). This indicates that null hypothesis is rejected, therefore using interview is effective in teaching simple present tense at SMAN 1 Soe Kabupaten Timur Tengah Selatan (TTS) NTT.